(untitled) (Journal of Fiber Bioengineering and Informatics, 2008)
This paper discusses a number of computational problems in textile/garment industry. These problems cover quality inspection of textile products, on-line process control and monitoring, process and material modeling and simulation, CAD for clothing and materials, and computerized management of production and supply chain. Recently, more attention has been paid to modeling and analysis of human related complex concepts such as well-being, textile comfort and marketing elements and their integration in the design of new products. The related computational techniques include classical methods such as statistics, physical law based analytical equations, classical signal and image processing and statistical pattern recognition, and intelligent techniques such as soft computing and data mining. The selection of specific computational techniques is strongly related to the nature of the problem of interest. An optimal solution to a complex textile or garment problem can be found by combining several complementary techniques in a suitable way.